2019
DOI: 10.15439/2019f101
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Predictive Models for Improving the Quality of Industrial Maintenance: An Analytical Literature Review of Maintenance Strategies

Abstract: Due to advances in machine learning techniques and sensor technology, the data driven perspective is nowadays the preferred approach for improving the quality of maintenance for machines and processes in industrial environments. Our study reviews existing maintenance works by highlighting the main challenges and benefits and consequently, it shares recommendations and good practices for the appropriate usage of data analysis tools and techniques. Moreover, we argue that in any industrial setup, the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Carvalho et al [13] presents a structured review of new literature presented in the years after 2014 and does so in a general manner, so the reader can get a general understanding of what moves within the field. Merkt et al [4] studies various maintenance approaches and the different applications that PdM might have. This is done by studying the full cycle of developing a successful model.…”
Section: The Field Of Prognostics and Health Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Carvalho et al [13] presents a structured review of new literature presented in the years after 2014 and does so in a general manner, so the reader can get a general understanding of what moves within the field. Merkt et al [4] studies various maintenance approaches and the different applications that PdM might have. This is done by studying the full cycle of developing a successful model.…”
Section: The Field Of Prognostics and Health Managementmentioning
confidence: 99%
“…[15] 2019 Review and proposition of efficient step-wise method for companies to deploy models on historical data and digital twins. [4] 2019 Review of various maintenance strategies, their application and use-cases with focus on the full cycle of creating PdM models. [16] 2018 An introduction to CDM with a strong overview over what possibilities it provides.…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Merkt reviewed maintenance approaches with applicability in the industrial environment. They found that literature did not inform as to which new AI technology based on ML methods and techniques is influencing and changing the maintenance approaches in the industrial setup [19]. Carvalho et al reviewed the use of ML techniques in PdM applications [20].…”
mentioning
confidence: 99%